Marriage money : the social shaping of money in marriage and banking - Singh, Supriya (Supriya S.), 1944- (St Leonards : Allen and Unwin, 1997)
The study of money as a social and cultural phenomenon. Studying marriage money. The boundaries of marriage money. The meanings of marriage money. Managing and controlling money in marriage. Banking separates multiple monies. Banking money. The gender of money.
Keywords: Australia; Economics; Banks; Women; Banks and banking -- Social aspects -- Australia; Women -- Australia -- Finance, Personal; Married people -- Australia -- Finance, Personal